Care work films and major Filipino stars experiences and meanings facility their production and consumption - Bantugan, Brian Saludes (2010)
"The study was pursued in response to a growing social reality. There is a fast increasing population of Filipino care workers that is now feeding the national economy and overtaking the nuer of male OFW's Care Workers, ranging from what the government calls "semi-skilled" domestic helpers and nannies, to "skilled" caregivers, to "professionals" like nurses and other health care workers, have recently become subjects of films that feature major film superstars in the country. This underscored the reality of a growing OFW (most of whom are care workers) market that could be key, in keeping the movie industry alive an sustaining other related industries. The use of superstars has a role in connecting to this emerging movie market. The use of care work as a theme or backdrop, if not the focal point, of the major-star led movies, point to this new market as the new source of film discourse.This study looked into the dynamics of care work film production and consumption by investigating experiences and meanings that are attached to major film stars and care work attached to drama films. Using Bakhtin's "Dialogism", Foucault's "Discourse", Gramsci's "Hegemony" and Gladwell "Tipping Point", the study was pursued employing in-depth interviews with the films' writers and directors, semi-structured interviews with overseas and local Filipinos, analysis of articles from Philippine Daily Inquirer, and film viewing. Results revealed that the care work film production is facilitated in different ways by the news, producers, and celebrities. The care work films take-off from themes coming from more general Filipino experiences that facilitate wider resonance with care work films. Overall, the films offer new opportunities for Filipino care workers to look upon their situation through the third person vantage point of films that re-present them. The films, on the other hand, offer a new venue for Filipino diaspora and care work discourses. The study impacts not only on the field of communication but also on migration studies, women's or gender studies, and researches related to the culture behind health care, now newly emerging fields of research in the Philippines and other developing countries."